Analisis Penerapan Sistem dan Prosedur Akuntansi dalam Pengelolaan Dana Desa: (Studi Kasus di Desa NagraksarioKecamatan Jampangkulon) - Ananda Taufik Hidayat; Ade Sudarma; Irfan Sophan Himawan (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to evaluate the accounting systems and procedures implemented at the Nagraksari village office. Using qualitative research methods, the study involves the village head, village staff, village secretary, village treasurer, and community leaders as informants. Data collection techniques include observation, interviews, and recording. The research findings indicate that the accounting system and financial management in Sukaramai Village are in accordance with the Ministry of Home Affairs Regulation Number 20 of 2018; however, village officials face difficulties in managing the accounting system due to a lack of human resources. The implementation of accounting systems and procedures in the management of village funds in Nagraksari Village complies with central government regulations based on Law Number 3 of 2024. It is hoped that village officials can optimize the use of the budget for the development and empowerment of the village community, allowing Nagraksari Village to grow according to its vision and mission while adhering to the regulations set by the central and regional governments.